Área de vida e seleção de habitat por sabiás (Turdus leucomelas, Turdidae) em ambiente urbanizado - Moraes, André Luiz Bitencourt [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The process of urbanization is one of the main human activities that alter natural environments, bringing numerous environmental impacts such as the reduction and fragmentation of natural habitats, causing loss of biodiversity, among other imbalances to the ecosystems. Urbanization can foster the homogenization of birds and the dominance of a few species, so in disturbed areas, plants have their reproductive investment dependent on a small group of bird species.Thrushes are one of such groups, possessing significant role in plant biodiversity maintenance in urban areas because of its high abundance and extent of frugivory, along with the frequent use of forest fragments in urban areas. Habitat structure and resource availability are important factors that influence bird communities both in natural environments and in environments modified by humans, influencing the size of the home ranges and the way that birds use the habitats. Thus, the aim of this study was to analyze the home range size of the thrush species Turdus leucomelas, and to investigate how environmental structure influences the habitat selection by these birds in an urban area. The study was conducted in the municipality of Rio Claro / SP, at the Universidade Estadual Paulista - Júlio de Mesquita Filho (UNESP) campus. Data collection took place from May/2014 to July/2015. Fourteen thrushes were monitored with radio transmitters, and a total of 1057 points of location were collected. The average values of the home ranges was 3.82 hectares as estimated by the Kernel 95%, and 3.26 hectares when estimated by the MCP. As for habitat selection all individuals positively selected forest habitat and negatively the other types. This shows the importance of conservation of vegetation in cities, because the maintenance of the individuals and biodiversity of birds in an urbanized environment is directly related to the local vegetation volume. So it is clear the need for policies that ...

O processo de urbanização é uma das principais ações antrópicas que alteram os ambientes naturais, resultando em inúmeras consequências ambientais, como a redução e fragmentação dos habitats naturais, causando perda da biodiversidade, entre outros desequilíbrios aos ecossistemas. A urbanização pode favorecer a homogeneização da avifauna e a dominância de algumas espécies, entre elas, estão os sabiás. Os sabiás são aves que possuem importante papel na manutenção da biodiversidade de plantas em áreas urbanas, graças à sua alta abundância e grau de frugivoria, juntamente com o uso frequente de fragmentos florestais. A estrutura do habitat e a disponibilidade de recursos são fatores importantes que influenciam as comunidades de aves tanto em ambientes naturais quanto em ambientes modificados pelo homem, com consequências para o tamanho da área de vida e na maneira como as aves utilizam o habitat. Sendo assim, o objetivo deste estudo foi analisar o tamanho da área de vida de sabiás da espécie Turdus leucomelas, além de investigar o quanto a estrutura do ambiente influencia na seleção de habitat por essas aves em um ambiente urbanizado. O estudo foi realizado no município de Rio Claro / SP, no campus da Universidade Estadual Paulista ―Júlio de Mesquita Filho (UNESP). As coletas de dados foram realizadas entre Maio/2014 e Julho/2015. Foram monitorados 14 sabiás equipados com radiotransmissores, e no total foram coletados 1057 pontos de localização das aves. O valor médio das áreas de vida foi de 3,82 hectares quando estimado pelo Kernel 95%, e 3,26 hectares quando estimado através do MPC. Quanto a seleção de habitat todos os indivíduos selecionaram positivamente o tipo de habitat bosque (árvores, arbustos e áreas que formam bosques contínuos) e negativamente os outros tipos, o que mostra a importância da conservação da vegetação dentro das cidades, pois a manutenção dos indivíduos e da...
Keywords: Birds; Ave; Sabiá (Ave) - Habitat; Urbanização; Biodiversidade